Assembly of Multiple Components in a Hybrid Microcapsule: Designing a Magnetically Separable Pd Catalyst for Selective Hydrogenation. Issue 38 (1st August 2014) - Amali, Arlin Jose; Sharma, Bikash; Rana, Rohit Kumar
Abstract In analogy to the role of long‐chain polyamines in biosilicification, poly‐L‐lysine facilitates the assembly of nanocomponents to design multifunctional microcapsule structures. The method is demonstrated by the fabrication of a magnetically separable catalyst that accommodates Pd nanoparticles (NPs) as active catalyst, Fe3O4 NPs as magnetic component for easy recovery of the catalyst, and silica NPs to impart stability and selectivity to the catalyst. In addition, polyamines embedded inside the microcapsule prevent the agglomeration of Pd NPs and thus result in efficient catalytic activity in hydrogenation reactions, and the hydrophilic silica surface results in selectivity in reactions depending on the polarity of substrates.